The Properties of Different Starches under the Influence of Glucono-Delta-Lactone at Different Concentrations - Afirah Mohd Shukri; Lai-Hoong Cheng (Foods, 2023)
In this study, glucono-delta-lactone (GDL), which is Generally Recognized as Safe (GRAS), was added to native starches to modify their physicochemical properties. The effects of GDL on the molecular weight, pasting properties, flow behavior, gel syneresis, and crystallization properties of potato, tapioca, and corn starches were investigated. GPC results showed that as the GDL concentration increased, the molecular weight of amylose increased, whereas that of amylopectin decreased. An analysis using the Rapid Visco Analyzer revealed that the addition of GDL improved the pasting properties of potato starch, with reduced peak viscosity and breakdown viscosity, and it also improved setback viscosity. On the other hand, tapioca starch degraded substantially after GDL addition, indicating a lower tendency for short-term retrogradation, as reflected in the lower setback viscosity. The effects of GDL on corn starch pasting properties were very similar to those observed for tapioca starch, but the changes were relatively subtle. In terms of flow behavior, GDL addition decreased and increased the flow index values of the potato and tapioca starch pastes, respectively. However, the effect of GDL addition on the flow index value of the corn starch paste was found to be insignificant. The results also showed that the percentage of syneresis under the influence of GDL depended on the starch botanical origin—that is, potato starch, 14–18%, tapioca starch, 10–13%, and corn starch, 17–20%—which was substantiated by crystallinity analysis. It was observed that GDL has the potential to be used for starch modification because it creates desirable functionalities with the advantage of being a green-labelled ingredient.